Varicella-zoster virus infection in pregnancy: a case of aseptic meningitis before 20 weeks gestation and review of the literature - Song, Gao; Cheng, Meng-Qun; Yang, Nan; Li, Rong; Zhang, Cai-Qiong; Chen, Si-Wei (Frontiers in Medicine, 2025)
BackgroundVaricella zoster virus (VZV) infection during pregnancy can lead to severe complications. However, cases complicated by aseptic meningitis in early pregnancy (<20 weeks) are extremely rare, and clinical management and pregnancy outcomes remain unclear.Case reportWe report a case of a 36-year-old pregnant woman who developed right upper abdominal pain, headache, and cough at 17 weeks of gestation, followed by clustered herpes zoster lesions in the right lumbar region and signs of meningeal irritation. Aseptic meningitis was confirmed by cerebrospinal fluid analysis (lymphocytes 184 × 106/L, protein 938 mg/L), and other etiologies were excluded by imaging. A 14-day course of acyclovir (5 mg/kg q8h) combined with prednisone achieved complete symptom resolution through a multidisciplinary collaboration (neurology, obstetrics, infectious diseases, pharmacy, and nursing). The patient experienced unexplained preterm delivery at 35 weeks, delivering a healthy male infant (2,680 g, Apgar 9–10-10) via cesarean section, with no sequelae at the 1-year follow-up.ConclusionThis represents the fourth reported case of VZV meningitis during pregnancy globally and the first occurring before 20 weeks of gestation with preterm delivery as a unique outcome. Key implications: (1) Early-to-mid gestation VZV infection may affect pregnancy outcomes through distinct mechanisms; (2) multidisciplinary management is critical for optimizing maternal-fetal prognosis; and (3) further investigation is needed to elucidate the relationship between infection timing and preterm birth.